2018
DOI: 10.1159/000490004
|View full text |Cite
|
Sign up to set email alerts
|

Do <b><i>Plantago lanceolata</i></b> Skin Prick Test-Positive Patients Display IgE to Genuine Plantain Pollen Allergens? Investigation of Pollen Allergic Patients from the North-East of France

Abstract: Background: English plantain (Plantago lanceolata) is an important weed pollen allergen source triggering allergic symptoms during summer. To elucidate genuine versus cross-reactive sensitization, we investigated IgE reactivity patterns and inhibition capacities of plantain-sensitized patients. Methods: Sera of 35 rhinoconjunctivitis patients from the north-east of France with positive skin prick tests (SPT) to Plantago lanceolata pollen were tested with clinically relevant allergen sources using ELISA, Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…they are sensitive to two or more allergens. This is consistent with the data from the US, where the exposure to numerous allergens simultaneously is also quite common, but with differences observed in scope of the dominant allergens in various households [63][64][65][66]. The study revealed that allergies as a result of exposure to environmental allergens are a major public health problem [67].…”
Section: Discussionsupporting
confidence: 89%
“…they are sensitive to two or more allergens. This is consistent with the data from the US, where the exposure to numerous allergens simultaneously is also quite common, but with differences observed in scope of the dominant allergens in various households [63][64][65][66]. The study revealed that allergies as a result of exposure to environmental allergens are a major public health problem [67].…”
Section: Discussionsupporting
confidence: 89%
“…SPT were performed on the forearm, in the absence of antihistamine intake for at least one week (Alk-Abello, Horsholm, Denmark). The test was considered positive if the greatest diameter of the wheal was >3 mm or >50% of the greatest diameter of the positive control (histamine solution at 1/1000) ( 29 ). Each positive test was recorded in mm, by measuring the greatest diameter of the wheal ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the general adolescent population in Austria, sensitization to the genuine and major allergen Pla l 1 was as high as 10.4% 666 . While an association with grass pollen or pan‐allergen sensitization is frequently observed, genuine Pla l 1‐related plantain allergy represents a true co‐sensitization 358,678,679 …”
Section: B03 – Weed Pollen Allergymentioning
confidence: 99%
“…666 While an association with grass pollen or panallergen sensitization is frequently observed, genuine Pla l 1-related plantain allergy represents a true co-sensitization. 358,678,679 High levels of reactivity to Mercurialis annua pollen ranging from 28-56% were observed in several areas of Spain. 680 Due to use of Chenopodium album in greening programs, the weed gained relevance in countries with desert and semi-desert areas accounting for up to 70.7% sensitization in asthmatic patients.…”
Section: (Amaranth)mentioning
confidence: 99%